Hydrochemical study of groundwaters from Botucatu city, Sao Paulo State, Brazil - Santos, C. A. dos [UNESP]; Bonotto, D. M. [UNESP]; Brebbia, C. A. (Wit Press, 2016)
This investigation was carried out at Botucatu city, Sao Paulo State, Brazil, and involved the study of groundwaters utilized for domestic consumption and industrial purposes. Botucatu city is situated in the recharge area of Guarani Aquifer System (GAS) in which the variegated quartzitic sandstones accumulated by eolian processes under desertic conditions and named Botucatu Formation were firstly described there. Notwithstanding, the municipality is drained by two hydrographic basins (Tiete River-north; Pardo River-south), groundwater has been extensively used there, justifying this investigation. The study involved the hydrochemical and radiometric analysis of 13 groundwater samples collected from tube wells exploiting different formations of the Parana sedimentary basin: Botucatu, Piramboia, Serra Geral, Marilia, Adamantina, and Santo Anastacio. The pH, silica, major ions, gross alpha radioactivity, gross beta radioactivity and activity concentration of dissolved Po-210 and Pb-210 were measured at LABIDRO-Isotopes and Hydrochemistry Laboratory, IGCE-UNESP-Rio Claro, Brazil, and compared with guideline reference values for drinking water quality. The results of the hydrochemical analysis were compared with the 1469 Ordinance of the Brazilian Health Ministry. The Piper diagram permitted to classify hydrochemically the samples, whereas the radioactivity levels were compared with the WHO guideline reference values for checking if they were appropriate for human consumption in terms of the parameters analyzed.
Keywords: groundwater composition; hydrochemistry; radioactivity; polonium